2008
DOI: 10.1016/j.brainres.2007.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Cirazoline, an alpha-1 adrenoreceptor agonist, on the firing rates of thermally classified anterior hypothalamic neurons in rat brain slices

Abstract: Peripheral exposure to LPS induces a biphasic fever thought to be initiated via vagal afferents to the preoptic area of the anterior hypothalamus (POAH), an important thermoregulatory control center in the brain. Previous studies have shown norepinephrine synaptically mediates this Prostaglandin E 2 (PGE 2 )-dependent change in temperature through the selective activation of alpha-2 adrenoreceptors (AR). However, there is clear evidence that alpha-1 AR activation of thermoregulatory hypothalamic neurons will r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Local warming of the POA evokes heat-loss responses (Magoun et al, 1938;Zhang et al, 1995), and the pioneering study of Nakayama et al (1961) and subsequent numerous studies have demonstrated the existence of thermosensitive neurons that respond to their own temperature in the POA. Although many studies on thermosensitive neurons have focused on areas in the medial side (such as the MPO, MPA or median preoptic nucleus (MnPO), for example, Hori et al, 1982;Koga et al, 1987;Travis and Johnson, 1993;Imbery et al, 2008) of the POA, some percentage of neurons in almost every brain area hitherto examined exhibit thermosensitivity, including those in the lateral POA (Travis and Boulant, 1989). Thermal stimulation of the medial POA would inevitably spread to nearby lateral areas.…”
Section: Discussionmentioning
confidence: 99%
“…Local warming of the POA evokes heat-loss responses (Magoun et al, 1938;Zhang et al, 1995), and the pioneering study of Nakayama et al (1961) and subsequent numerous studies have demonstrated the existence of thermosensitive neurons that respond to their own temperature in the POA. Although many studies on thermosensitive neurons have focused on areas in the medial side (such as the MPO, MPA or median preoptic nucleus (MnPO), for example, Hori et al, 1982;Koga et al, 1987;Travis and Johnson, 1993;Imbery et al, 2008) of the POA, some percentage of neurons in almost every brain area hitherto examined exhibit thermosensitivity, including those in the lateral POA (Travis and Boulant, 1989). Thermal stimulation of the medial POA would inevitably spread to nearby lateral areas.…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al (28) found this response after acute NE injection in the guinea pig PO/AH; Gisolfi and Christman (8) (rat PO/AH) and Myers et al (21) (cat PO/AH) also found hypothermic effects. Quan and colleagues (29) reported that this hypothermic response is mediated by ␣ 2 -noradrenergic receptors in the PO/AH (29), while studies agonizing ␣ 1noradrenergic receptors found rapid rises in T core (7,12). From literature it becomes clear that ␣-noradrenergic receptors evoke differentially mediated T core responses; for example, the ␣ 1noradrenergic receptor agonist cirazoline induced a prompt T core rise, whereas the selective ␣ 2 -noradrenergic receptor agonist induced a fall in T core that lasted for at least 3 h (7).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that warm-sensitive neurons in the mPOA are more abundant than cold-sensitive neurons (Dean and Boulant, 1989); our recent studies as well as those of others have demonstrated that the functional role of mPOA warm-sensitive neurons in heat production involves the inhibitory control of thermogenesis (Chen et al, 1998;Ishiwata et al, 2002Ishiwata et al, , 2005Zhang et al, 1995). Interestingly, it has been reported that NA (Watanabe et al, 1986) or an α 1 -adrenoceptor agonist cirazoline inhibits the activity of warm-sensitive neurons in the mPOA in the rat slice preparation (Imbery et al, 2008), and that perfusion of cirazoline into the mPOA induced prompt hyperthermia in an in vivo microdialysis study (Feleder et al, 2004). Taking these observations into account the α 1 -adrenoceptor mediated inhibition of warm-sensitive neurons in the mPOA probably activates a heat production response against acute cold environments in normaltemperature housed animals.…”
Section: Discussionmentioning
confidence: 87%